Предмет: Алгебра,
автор: ЛукаМегурине
Упрости выражения.
1. 8–(y+4)(y–4).
2. (3b+5c)(5c–3b) + 9b^2
3. 9x(2–x)+(3x+2)^2.
4. 4(x^2+4)–(5x–4)^2.
5. 3(x+y)^2–6xy.
6. (x–3)^2–(x+3)(3–x).
Ответы
Автор ответа:
14
1. 8–(y+4)(y–4)=8-(y²-16)=8-y²+16=-y²+24
2. (3b+5c)(5c–3b) + 9b^2=(5c+3b)(5c-3b)+9b²=25c²-9b²+9b²=
25c²
3. 9x(2–x)+(3x+2)^2=18x-9x²+9x²+12x+4=
30x+4
4. 4(x^2+4)–(5x–4)^2=4x²+16-(25x²-40x+16)=4x²+16-25x²+40x-16=
-21x²+40x
5. 3(x+y)^2–6xy=3(x²+2xy+y²)-6xy=
3x²+6xy+3y²-6xy=3x²+3y²
6. (x–3)^2–(x+3)(3–x)=x²-6x+9-(3+x)(3-x)=
x²-6x+9-9+x²=2x²-6x
2. (3b+5c)(5c–3b) + 9b^2=(5c+3b)(5c-3b)+9b²=25c²-9b²+9b²=
25c²
3. 9x(2–x)+(3x+2)^2=18x-9x²+9x²+12x+4=
30x+4
4. 4(x^2+4)–(5x–4)^2=4x²+16-(25x²-40x+16)=4x²+16-25x²+40x-16=
-21x²+40x
5. 3(x+y)^2–6xy=3(x²+2xy+y²)-6xy=
3x²+6xy+3y²-6xy=3x²+3y²
6. (x–3)^2–(x+3)(3–x)=x²-6x+9-(3+x)(3-x)=
x²-6x+9-9+x²=2x²-6x
Похожие вопросы
Предмет: Химия,
автор: VeronikaLe
Предмет: Физика,
автор: magomedsaidov43
Предмет: Математика,
автор: vvhhvyvy
Предмет: Другие предметы,
автор: dasha280701
Предмет: Русский язык,
автор: armanarman2009